Beauty and the beast lost in a book an enchanting original story - Donnelly, Jennifer (Beauty and the beast, 2017)
Disney Beauty and the Beast Lost in a Book. Hidden in the Beast's library is a very mysterious book. Belle is about to discover it and visit a glittering new world. But is everything in that world what it seems? And will Belle be able to find her way home? Or will the story take hold of her-and never let her go?